1999
DOI: 10.1007/s001250051218
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of peroxisome proliferator-activated receptorγ expression by inflammatory cytokines and its reversal by thiazolidinediones

Abstract: Impairment of insulin action (insulin resistance) is frequently observed in Type II (non-insulin-dependent) diabetes mellitus as well as in wasting syndromes including neoplastic, inflammatory and chronically infectious diseases [1,2]. Previous studies suggest that inflammatory cytokines, such as tumour necrosis factor-a (TNF-a) [3], interleukin-1 (IL-1) [4], , leukaemia inhibitory factor (LIF) [6] and transforming growth factor-b (TGF-b) [7] are involved in the development of insulin resistance. Clinical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…In in vitro studies, it has been reported that thiazolidinediones increase glucose uptake in 3T3-F442A and 3T3-L1 adipocytes by increasing GLUT4 and/or GLUT1 content (9,10). In mature adipocytes, troglitazone has also been reported to increase GLUT4 mRNA levels (11). These in vitro and in vivo studies could not distinguish between the increases in glucose transporters associated with the enhancement of adipocyte differentiation and those resulting from the direct effects of the thiazolidinedione on mature adipocytes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In in vitro studies, it has been reported that thiazolidinediones increase glucose uptake in 3T3-F442A and 3T3-L1 adipocytes by increasing GLUT4 and/or GLUT1 content (9,10). In mature adipocytes, troglitazone has also been reported to increase GLUT4 mRNA levels (11). These in vitro and in vivo studies could not distinguish between the increases in glucose transporters associated with the enhancement of adipocyte differentiation and those resulting from the direct effects of the thiazolidinedione on mature adipocytes.…”
Section: Discussionmentioning
confidence: 94%
“…In in vitro studies, it has been reported that thiazolidinediones increased glucose uptake in 3T3-F442A and 3T3-L1 adipocytes by increasing GLUT4 and/or GLUT1 content (9,10). In mature adipocytes, troglitazone has also been reported to increase GLUT4 mRNA levels (11). Furthermore, thiazolidinediones have been suggested to modulate intrinsic activity and translocation of glucose transporters (12).…”
mentioning
confidence: 99%
“…IL-6 could affect functions of lipid and muscle cells [43,44,45]. In contrast lipid tissue is a major source of IL-6 [46,47] and possibly also of sIL-6R [48].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that PPARγ expression is downregulated in the lung and vascular endothelium in rodent models of septic shock and that treatment with PPARγ ligands reverses the sepsis-induced reduction (1). In adipose tissue, PPARγ expression decreased after mice were challenged in vivo with endotoxin, and cytokine-induced suppression of PPARγ was reversed with synthetic agonists (5,6). However, it remains unclear what mechanisms lead to a decrease in PPARγ activity in sepsis.…”
Section: Introductionmentioning
confidence: 99%